The effect of firm cash holdings on monetary policy - Adão, Bernardino (2022)
Firm cash holdings increased substantially from 1980 to 2017. We study the implications of the increase in firm cash holdings on monetary policy. We introduce a model that takes the distribution of firm cash holdings as an input. We find that the interest rate channel of the transmission of monetary policy becomes more powerful, as the impact of monetary policy over real interest rates increases. The time for the real interest rate to return to its initial value increases three times. Given the current large firm cash holdings, our results imply that monetary policy changes should be made gradually.